Procrastination, Academic Success and the Effectiveness of a Remedial Program - Maria De Paola; Vincenzo Scoppa (Institute for the Study of Labor (IZA), 2014)
Procrastination produces harmful effects for human capital investments and studying activities. Using data from a large sample of Italian undergraduates, we measure procrastination with the actual behaviour of students, considering the delay in finalizing their university enrolment procedure. We firstly show that procrastination is a strong predictor of students' educational achievements. This result holds true controlling for quite reliable measures of cognitive abilities, a number of background characteristics and indicators of students' motivation. Secondly, we investigate, using a Regression Discontinuity Design, the effects of a remedial program in helping students with different propensity to procrastinate. We show that the policy especially advantages students who tend to procrastinate, suggesting that also policies not directly aimed at handling procrastination can help to solve self-control problems.
Keywords: D03; I21; D91; J01; J24; 330; procrastination; self-control; time preferences; time consistency; impatience; human capital; academic success; dropout; remedial courses